Correlações entre parâmetros microestruturais, parâmetros térmicos e resistência mecânica de ligas Sn- Bi e Sn-Bi-(Cu,Ag) - Silva, Bismarck Luiz (2016)
The present research aims to develop a theoretical/experimental analysis of the combined effects of solidification thermal parameters, Bi content and addition of ternary elements (Cu, Ag) on the final microstructure aspects and on the final mechanical resistances of directionally solidified Sn-Bi, Sn-Bi-Ag and Sn-Bi-Cu solder alloys under transient heat flow conditions. Hence, experimental interrelations between microstructure and thermal parameters and between mechanical properties and microstructure could be established. The microstructures regarding the Sn-34wt.%Bi and Sn-52wt.%Bi alloys show the presence of β-Sn dendrites with Bi precipitates on their own, being enveloped by a lamellar binary Sn-Bi eutectic. The Sn-58wt.%Bi eutectic alloy show a variety of microstructures along the length of the directionally solidified casting, which includes binary eutectic, Bi plates, Bi trifoils and fishbone eutectic. In the case of the ternary Sn-Bi-Ag and Sn-Bi-Cu chemistries, microstructures are constituted by β-Sn dendrites decorated with Bi particles, Bi-Sn eutectic and Cu6Sn5 and Ag3Sn intermetallic particles for the Cu and the Ag bearing alloys, respectively. Experimental growth laws have been derived for both dendritic (λ1, λ2, λ3) and eutectic (λfine, λcoarse) arrangements considering the following alloys: binary Sn-34wt.%Bi, Sn-52wt.%Bi e Sn-58wt.%Bi alloys and ternary Sn- 34wt.%Bi-0.1wt.%Cu, Sn-34wt.%Bi-0.7wt.%Cu e Sn-33wt.%Bi-2wt.%Ag. Considering the binary Sn-Bi, it has been observed that increasing Bi content (34wt.%-->52wt.%-->58wt.%Bi), may cause a decrease on both strength and ductility, except for the sample at P=6mm of the Sn-52wt%Bi alloy. Hall-Petch type functional correlations have been able to represent the evolution of the tensile mechanical properties for the examined Sn-Bi and Sn-Bi-X alloys.